Fox Creek : a novel - Krueger, William Kent (New York : Atria Books, 2022)
The latest in the New York Times bestselling Cork O'Connor Mystery Series follows Cork in a race against time to save his wife, a mysterious stranger, and an Ojibwe healer from bloodthirsty mercenaries. The ancient Ojibwe healer Henry Meloux has had a vision of his death. As he walks the Northwoods in solitude, he tries to prepare himself peacefully for the end of his long life. But peace is destined to elude him as hunters fill the woods seeking a woman named Dolores Morriseau, a stranger who had come to the healer for shelter and the gift of his wisdom. Meloux guides this stranger and his great niece, Cork O'Connor's wife, to safety deep into the Boundary Waters, his home for more than a century. On the last journey he may ever take into this beloved land, Meloux must do his best to outwit the deadly mercenaries who follow. Meanwhile, in Aurora, Cork works feverishly to identify the hunters and the reason for their relentless pursuit, but he has little to go on. Desperate, Cork begins tracking the killers but his own skills as a hunter are severely tested by nightfall and a late season snowstorm. He knows only too well that with each passing hour time is running out. But his fiercest enemy in this deadly game of cat and mouse may well be his own deep self-doubt about his ability to save those he loves
Series information and numbering from GoodReads.com
BPL: David Winn Bishop and Isabel MacPherson Bishop Memorial Fund.
Keywords: O'Connor, Cork -- (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Fiction; Ojibwa Indians -- Fiction; Soldiers of fortune -- Fiction; Married people -- Fiction; Indian healers -- Fiction; Hunters -- Fiction; Minnesota -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Novels